APLIKASI STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL MENENGAH (SAK-EMKM) BAGI PELAKU USAHA COUNTER PULSA DAN HANDPHONE - firmansyah, irman; Wahid, Nisa Noor (LPPM Univeristas Siliwangi, 2024)
The objectives and specific targets of this activity are for Counter Pulsa and Handphone which is currently very vibrant. The importance of knowing the profits derived from the results of his efforts to make a professional organization of the Indonesian Institute of Accountants (IAI) issued ED SAK-EMKM as the financial accounting standards of SMEs in Indonesia. so that the perpetrators of SMEs should understand how to create financial statements in accordance with accounting standards of SMEs in Indonesia. The problem raised is the counter pulse counterpart especially the partner of DN Cell does not know how to prepare the financial statements in accordance with the standard whereas to know the lapa obtained from the business it must be made a good financial statements, and they do not know how to start from where . Community service activities are implemented within 3 months from signing MoU to reporting. The method of solving community service problem is by providing assistance to one of the pulp and Hanphone business actors in preparing the financial report for 3 months with the final result is the financial report of MSME in accordance with accounting standard (SAK-EMKM). Based on the results of assistance, the partner becomes aware of the importance of financial statements and able to prepare their own financial statements in accordance with the standards set by the Indonesian Institute of Accountants (IAI). Partners can see the development of the company since before the mentoring and after the mentoring as it can see the good financial statements.